Asuhan Keperawatan Jiwa Pada Penyintas Erupsi Gunung Semeru Dengan Core Problem Ansietas Di Hunian Tetap (Huntap) - Butar Butar, Camelita; Hardayati, Yunita Astriani (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
The eruption of Mount Semeru is one of the natural disasters that has an impact on environmental damage, property loss, and even loss of life. Survivors of the eruption of Mount Semeru are at risk of experiencing mental health problems, one of which is anxiety. Preschool children are an age group that is vulnerable to anxiety. The purpose of this case study is to see the picture of mental health problems in preschool children who are survivors of Semeru and to observe changes in signs of anxiety symptoms in children after being given mental nursing care consisting of deep breathing relaxation techniques, distraction, and education. Researchers used the SDQ (Strengths and Difficulties Questionnaire) questionnaire to measure children's mental health problems and a knowledge questionnaire to measure the level of maternal knowledge in stimulating children's social development. The results of the study showed that 14% of children had normal difficulty scores, 29% had borderline scores, 57% had abnormal scores. For the difficulty score, 43% had borderline scores, and 57% had abnormal scores. Mental health nursing care can reduce anxiety in Semeru survivor children in Huntap and increase mothers' knowledge in providing social stimulation to children. Nurses have a role in improving mental health after a disaster through promotive, preventive and rehabilitative intervention.